The central vein sign in the diagnosis of multiple sclerosis - Sh. R. Nabiev; S. A. Dzhukkaeva; M. Sh. Asvedov; O. N. Voskresenskaya (Неврология, нейропсихиатрия, психосоматика)
Objective: to determine the specificity and sensitivity of the central vein sign (CVS) for the diagnosis of multiple sclerosis (MS). Material and methods. We analyzed 76 patients. The main group consisted of 40 patients with a confirmed diagnosis of MS according to the McDonald criteria, 2017. The comparison group included 20 patients with migraine and 16 patients with cerebral microangiopathy. All patients underwent a standardized MRI scan of the brain, including 3D FLAIR and SWI modes. The total number of T2/FLAIR hyperintense lesions in the brain and the number of lesions with CVS were calculated. Results. In the group of MS patients, the total and relative number of lesions with CVS was higher than in the comparison group (p<0.001). The 40% lesion rule had a sensitivity of 97.5% and a specificity of 94.4%. The sensitivity of the 3-lesion rule was 92.5% and the specificity 66.7%. The use of the 5-lesion rule had a sensitivity of 75% and a specificity of 83.7%. Conclusion. The data obtained indicate a significant diagnostic role for SCV in MS. The use of the 5-lesion rule provides high sensitivity and specificity with relative ease of use.